Analisis Hubungan Variabel Makroekonomi dan ISSI Terhadap NAB Reksa Dana Syariah di Indonesia Pada Tahun 2012-2024 - Muthia, Annisa; Kamarni, Neng (Akuntansi & Ekonomika, 2025)
Sharia mutual fund Net Asset Value (NAV) functions as a critical indicator used to assess the performance of Indonesia’s sharia-compliant financial instruments, where its movements are greatly influenced by macroeconomic conditions and financial market dynamics. Using the VECM model, the analysis explores how the Indonesian Sharia Stock Index and various macroeconomic factors relate to and affect the NAV of sharia mutual funds in both the short and long term during the period January 2012–December 2024. The findings indicate that, in the short run, inflation reduces NAV, whereas the exchange rate and ISSI contribute positively, and interest rates do not exhibit significant effects. Over the long term, NAV is pressured downward by inflation and interest rates, while the exchange rate and ISSI maintain their positive influence.